PWE-021 Anal advancement flap versus lateral internal sphincterotomy for chronic anal fissure- a systematic review and meta-analysis. (17th June 2017) - Sahebally, S; Wlash, S; Mahmood, W; Aherne, T; Joyce, M
Abstract : Introduction: Chronic anal fissures (CAF) are common and associated with reduced quality of life. Lateral internal sphincterotomy (LIS) is the surgical treatment of choice but carries a significant risk of anal incontinence. Anal advancement flap (AAF) has been advocated as an alternative, 'sphincter-preserving' procedure. We aimed to perform a systematic review and meta-analysis to compare the efficacy of both techniques in the treatment of CAF. Method: The online databases of PubMed/Medline, CINAHL, EMBASE and Cochrane Central Register of Controlled Trials were searched from inception to January 2017. All studies that investigated and reported outcomes of LIS and AAF for treatment of CAF were included. The primary outcome measure was anal incontinence while secondary outcomes included unhealed fissure and wound complication rates. Random effects models were used to calculate pooled effect size estimates. Results: Four studies (2 randomised controlled trials and 2 retrospective studies) describing 300 patients (150 LIS, 150 AAF) fulfilled our inclusion criteria. There was significant clinical heterogeneity among the trials. On random effects analysis, AAF was associated with a significantly lower rate of anal incontinence compared to LIS (OR=0.06, 95% CI=0.01 to 0.36, p=0.002). However, there were no statistically significant differences in unhealed fissure (OR=2.21, 95% CI=0.25 to 19.33, p=0.47) or wound complication rates (OR=1.41, 95% CI=0.50 to 4.99 p=0.51) between AAF and LIS. Conclusion: AAF is associated with less incontinence, similar wound complications and a non-significant higher rate of unhealed fissures compared to LIS. However, further well-executed, multi-centre randomised trials are required to provide stronger evidence. Disclosure of Interest: None Declared